An Investigation of the Variables That Influence Female Counselors' Work–Family Conflict. Issue 2 (7th June 2019) - Eckart, Emeline C.; Ziomek‐Daigle, Jolie
Abstract : This study investigated the relationship between female counselors' work–family conflict and their demographic, occupational, and family characteristics. Female counselors' engagement in work and family and the conflict that results were assessed in 2 directions: work interfering with family (WIF) and family interfering with work (FIW). Autonomy and hours spent at work significantly contributed to counselors' WIF scores. Autonomy; age of the youngest child; care of elderly, ill, or special needs family members; and support contributed to counselors' FIW scores.